PROBABLE MODE OF ACTION OF KALYANAKA GHRITA IN UNMADA (INSANITY) BASED ON ANALYSIS OF RASA PANCHAKA OF INGREDIENTS- A REVIEW - T. P, Sinimol (International Journal of Ayurveda and Pharma Research, 2019)
Aim: This review article is an attempt to analyse the probable mode of action of Kalyanaka ghrita in psychiatric conditions. Background: Unmada is a term that represents broad classes of mental ailments in Ayurvedic literature. Mental disorders impose an enormous burden on society, accounting for almost one in three years lived with disability globally. According to the WHO, every year, almost one million people die from suicide; a "global" mortality rate of 16 per 1,00,000 or one death every 40 seconds. Kalyanaka ghrita is a time tested and clinically proven polyherbal formulation which is widely and effectively used by Ayurvedic physicians in the management of psychiatric conditions. Results: While analysing the Rasapanchaka (Ayurvedic Principles of Drug-Action), it is found that of the 28 ingredients, 15 drugs are having Tikta rasa, 22 with Laghu guna, 19 with Ushna veerya and 18 with Katu vipaka. Considering Doshaharatwa, 12 drugs are Kaphapittahara. All these properties are against Kapha dosha. Conclusion: Kalyanaka ghrita may be more effective in the management of Kaphaja unmada, among all the 6 varieties of Unmada. Clinical Significance: Analysis of mode of action leads us to the inference that Kalyanaka ghrita may be more effective in the management of Kaphaja unmada, characterised by slow or weak voice and body movements, anorexia, desire for women (sex) and solitude, excessive sleep, vomiting, dribbling of saliva, symptoms pronounced just after intake of food, whitish discoloration of nails constitute Kaphaja unmada, a classical example being depression.